SAT0088 NO INCREASED RISK OF FALLS IN PATIENTS TREATED WITH BIOLOGICS COMPARED TO THOSE UNDER CSDMARDS. (2nd June 2020) - Rudi, T.; Schaefer, M.; Manger, B.; Zink, A.; Strangfeld, A.
Abstract : Background: Adults with rheumatoid arthritis (RA) have an increased risk of falling. Previous studies on causes of falls have neither sufficiently nor adequately considered the effects of bDMARDs. In addition, a risk analysis of the individual substances has been lacking until now. Objectives: To analyze the fall risk under exposure to TNFi's, abatacept (ABA), rituximab (RTX) and tocilizumab (TOC) in comparison to csDMARDs taking co-medication and other risk factors such as disease activity, comorbidities and other biological risks into account. Methods: Data of RA patients observed in RABBIT from 01/2009 - 02/2018 with a follow-up of up to 5 years was used for the analysis. In accordance with consensus guidelines, a fall was defined as "an unexpected event in which participants come to rest on the ground, floor or other lower level" [1]. Effects of bDMARDs were examined using "inverse probability weighting" (IPW) with time-varying treatment on a monthly basis. Directed acyclic graphs were applied to support causal considerations. Results: The percentage of patients with falls (2.7%) was significantly lower than the previously reported 10% and 50% [2]. This underreporting is explained by the fact that falls in RABBIT are reported by the physicians and are not recorded in patient diaries. In line with other studies, falls occurred with older age, longer disease duration, poorer physical function and higher DAS28. Patients with a higher number of comorbidities had a significantly higher risk of falling. The number of patients treated with analgesics was higher in the fall group and fallers had higher glucocorticoid doses. However, the values for pain and fatigue were comparable between the two groups (Table 1 ). The descriptive analysis showed that patients starting second / third line biologics therapy had a shorter duration from the initiation of treatment to the fall event than patients starting with csDMARDs. None of the regression models showed an increased risk for biologics compared to csDMARDs. Conclusion: None of the inferential analyses could demonstrate an increased risk of falling for any of the bDMARDs compared to csDMARDs. Although descriptive analyses pointed to an earlier fall event in patients treated with second-/third line biologics, these results could be explained by their particular characteristics. These patients tended to be older and were more affected by RA. This suggests that these risks override the effects of bDMARDs. References: [1] Lamb SE, et al. Journal of the American Geriatrics Society. 2005;53(9):1618-22. [2] Brenton-Rule A, et al.Seminars in Arthritis and Rheumatism. 2015;44(4):389-98. Acknowledgments: RABBIT is supported by a joint, unconditional grant from AbbVie, Amgen, BMS, Fresenius Kabi, Hexal, Lilly, MSD, Mylan, Pfizer, Roche, Samsung Bioepis, Sanofi-Aventis, and UCB. Disclosure of Interests: Tatjana Rudi: None declared, Martin Schaefer: None declared, Bernhard Manger Consultant of: Lilly, Celgene, Janssen, MSD, UCB, Speakers bureau: AbbVie, AstraZeneca, Alexion, Berlin-Chemie, BMS, Celgene, Chugai, Sanofi-Genzyme, GSK, Janssen, Lilly, MSD, Novartis, Pfizer, Roche, SOBI, UCB, Angela Zink Speakers bureau: AbbVie, Amgen, BMS, Gilead, Hexal, Janssen, Lilly, MSD, Pfizer, Roche, Sanofi Aventis, UCB, Anja Strangfeld Speakers bureau: AbbVie, BMS, Pfizer, Roche, Sanofi-Aventis